Optimizing speedup performance of computational hydrodynamic simulations with UPC programming model - Chew, Alvin Wei Ze (2022)
In this study, we exploit the advantages of Berkeley's Unified Parallel C (UPC) programming model to optimize the speedup performance of computational hydrodynamic (CHD) simulations, which constitute an important class of modelling tool for hydraulic engineering applications. A two-dimensional (2D) numerical model, termed UPC-CHD, is developed using the conservative forms of the Navier-Stokes (NS) continuity, momentum, and energy equations for viscous, incompressible, and adiabatic flow cases with the UPC model. The following numerical schemes are adopted for discretization in UPC-CHD: (1) a 2-step Lax-Wendroff explicit scheme for the temporal term; (2) a Roe linear approximation with a 3rd-order upwind biased algorithm for the convective fluxes; and (3) a central-differencing scheme for the viscous fluxes. The obtained speedup results demonstrate that UPC-CHD with the affinity principle achieves good speedup performance when compared to the serial algorithm, with an average value of 0.8 per unit core (thread) until 100 processor cores when simulating the Couette, Blasius boundary layer, and Poiseuille flows on a 2D domain of 100 million grids. Finally, we also investigate the effects of varying domain size on the speedup performances of UPC-CHD for the same flow conditions.